Direct Benefit Transfer: The Great Technological Move of India - Ahmad, Showkat (RADINKA JAYA UTAMA PUBLISHER, 2022)
Direct Benefit Transfer (DBT) has been used to deliver over 450 schemes to over 900 million people. Since 2016, the government has deposited nearly 65% of the welfare and subsidy budget directly into beneficiaries' accounts. DBT will undoubtedly meet the government's and people's expectations, especially those of the poor and unfortunate. The research objectives are to understand the meaning and initiatives of DBT and to analyze the Pros and Cons of DBT. A qualitative approach has been used to analyze the secondary data that has been gathered from reputable sources such as books and websites on the internet and newspaper articles, as well as various international journals and magazines. We hope that more schemes will be covered by DBT and that the entire country and its people will receive benefits without delay or flaws. As a result, the government must make a concerted effort in various areas of planning to improve the lives of the poor and powerless in society. In this way, DBT helps create an environment where people can live long, healthy, and creative lives. This paper examines the role of DBT.